Greenland Ice Surface Temperature, Surface Albedo, and Water Vapor from MODIS Comparison Tool ... - Felikson, Denis; Simon, Erika; Hall, Dorothy K.; DiGirolamo, Nicolo; Snitzer, Elliot (Ghub, 2021)
This tool compares Greenland Ice Sheet surface temperature from a model against observations. The observations are compiled in a multilayer data product called Multilayer Greenland Ice Surface Temperature, Surface Albedo, and Water Vapor from MODIS, Version 1 (MODGRNLD; https://nsidc.org/data/MODGRNLD). This dataset includes both monthly and daily resolutions. Currently, this tool uses modeled ice sheet surface temperature from the Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2; https://gmao.gsfc.nasa.gov/reanalysis/MERRA-2). An example of this modeled data is provided with the tool at monthly resolution for January, 2015. This tool interpolates MERRA-2 data to the higher-resolution MODGRNLD observations, creates a map plot and a histogram of the differences in ice sheet surface temperature. The user is able to download both plots. Files downloaded by this tool are netCDF4(.nc4) files. They are stored in the /data directory under the path /data/groups/ghub/tools/modgrnld. ...